Strategies for forming moderate religious attitudes among students at Kartika I-2 High School in Medan and Free Methodist High School in Medan - Muhammad Khairi Amri; Muhammad Qorib (Indonesian Journal Education, 2026)
Kartika 1–2 High School in Medan and Free Methodist High School in Medan promote religious moderation through curriculum integration, school culture, and extracurricular programs. This study aims to analyze the strategies employed by Islamic Religious Education teachers and their collaboration with teachers of other religious subjects in fostering religious moderation, as well as to examine the challenges encountered in implementing these values within the K13 and Merdeka curricula. The research adopts a qualitative approach, with data collected through interviews, observations, and documentation, and analyzed using a deductive method. The findings indicate that religious moderation is strengthened through several key strategies: integrating moderation values into curriculum documents and classroom instruction; implementing project-based learning that promotes tolerance, mutual respect, and interreligious cooperation; organizing interfaith extracurricular activities and social service programs; and reinforcing moderate attitudes through religious celebrations, counseling, and school culture. The study also identifies several challenges, including external social influences and varying levels of parental involvement. Overall, the implementation of these strategies has contributed to improved student understanding and practice of religious moderation, as reflected in reduced SARA-based bullying, stronger interreligious solidarity, and more inclusive student leadership processes.